Problematičnost določbe o avtorskih delih iz delovnega razmerja v 101. členu ZASP za odprto znanost - Bogataj Jančič, Maja (Delavci in delodajalci, 2025)
Article 101 of the Slovenian Copyright and Related Rights Act (hereinafter: ZASP) establishes a presumption of transfer of material copyright from an employee to an employer when an employee creates a copyright work in the performance of his or her duties or following instructions given by his or her employer. At the Open Data and Intellectual Property Institute ODIPI, in 2024 and 2025, with the support of the Knowledge Rights 21 programme, we prepared a study on barriers and enablers for open science in copyright law, within the framework of which we analyzed the copyright legislation of three countries. This article will examine the problematic nature of the provision in Article 101 of ZASP, which can pose a significant barrier to open science practices, although, in certain cases, it may also serve as an enabler. The conclusion will present the proposed approach to solving the problem.
Keywords: avtorska dela iz delovnega razmerja; Avtorske pravice; copyright; incentives for open science; material copyright; materialne avtorske pravice; obstacles to open science; odprta znanost; open science; ovire za odprto znanost; spodbude za odprto znanost; works of authorship from employment